Tetrahedral framework nucleic acids/hyaluronic acid-methacrylic anhydride hybrid hydrogel with antimicrobial and anti-inflammatory properties for infected wound healing - Cai Qi; Qiang Sun; Dexuan Xiao; Mei Zhang; Shaojingya Gao; Bin Guo; Yunfeng Lin (Nature Publishing Group, 2024)
Abstract Bacterial resistance and excessive inflammation are common issues that hinder wound healing. Antimicrobial peptides (AMPs) offer a promising and versatile antibacterial option compared to traditional antibiotics, with additional anti-inflammatory properties. However, the applications of AMPs are limited by their antimicrobial effects and stability against bacterial degradation. TFNAs are regarded as a promising drug delivery platform that could enhance the antibacterial properties and stability of nanodrugs. Therefore, in this study, a composite hydrogel (HAMA/t-GL13K) was prepared via the photocross-linking method, in which tFNAs carry GL13K. The hydrogel was injectable, biocompatible, and could be instantly photocured. It exhibited broad-spectrum antibacterial and anti-inflammatory properties by inhibiting the expression of inflammatory factors and scavenging ROS. Thereby, the hydrogel inhibited bacterial infection, shortened the wound healing time of skin defects in infected skin full-thickness defect wound models and reduced scarring. The constructed HAMA/tFNA-AMPs hydrogels exhibit the potential for clinical use in treating microbial infections and promoting wound healing.